A novel truncating mutation in FLNA causes periventricular nodular heterotopia, Ehlers-Danlos-like collagenopathy and macrothrombocytopenia - Ieda, Daisuke; Hori, Ikumi; Nakamura, Yuji; Ohshita, Hironori; Negishi, Yutaka; Shinohara, Tsutomu; Hattori, Ayako; Kato, Takenori; Inukai, Sachiko; Kitamura, Katsumasa; Kawai, Tomoki; Ohara, Osamu; et al. (Brain & development (Tokyo. 1979), 2018)
Filamin A (FLNA) is located in Xq28, and encodes the actin binding protein, filamin A. A mutation in FLNA is the most common cause of periventricular nodular heterotopia (PVNH), but a clear phenotype-genotype correlation has not been established. Indeed, some patients with a FLNA mutation have recently been shown to additionally have Ehlers-Danlos-like collagenopathy or macrothrombocytopenia. In an attempt to establish a clearer correlation between clinical symptoms and genotype, we have investigated a phenotype that involves thrombocytopenia in a patient with a truncation of the FLNA gene. We present the case of a 4-year-old girl who, at birth, showed a ventral hernia. At 2 months of age, she was diagnosed with patent ductus arteriosus (PDA) and aortic valve regurgitation. At 11 months, she underwent ligation of the PDA. She was also diagnosed with diaphragmatic eventration by a preoperative test. At 19 months, motor developmental delay was noted, and brain MRI revealed bilateral PVNH with mega cisterna magna. Presently, there is no evidence of epilepsy, intellectual disability or motor developmental delay. She has chronic, mild thrombocytopenia, and a platelet count that transiently decreases after viral infection. Dilation of the ascending aorta is progressing gradually. Genetic testing revealed a de novo nonsense heterozygous mutation in FLNA (NM_001456.3: c.1621G > T; p.Glu541Ter). Immunofluorescence staining of a peripheral blood smear showed a lack of filamin A expression in 21.1% of her platelets. These filamin A-negative platelets were slightly larger than her normal platelets. Our data suggests immunofluorescence staining of peripheral blood smears is a convenient diagnostic approach to identify patients with a FLNA mutation, which will facilitate further investigation of the correlation between FLNA mutations and patient phenotype.